Testing of a multi-theory model (MTM) to determine factors associated with the initiation and maintenance of adequate sleep behaviour among students from a Southeastern US medical school - Manoj Sharma; Robert Davis; Anjali Chandra; Amanda H Wilkerson; Vinayak K Nahar; Krishen Dennis Samuel; Vipina B Nair; Syed Siraj A Quadri; Joshua Mann (BMJ Public Health)
Background The quality of one’s sleep directly affects both physical and cognitive performance as well as overall physiologic health. Sleep deprivation occurs when a person does not get enough sleep. According to recent estimates, one in five Americans does not get enough sleep. Anybody who lacks sleep might suffer negative impacts, but those who work in high-stress, high-risk jobs that need greater concentration and focus are most affected. One group that fits that criteria is medical students. The purpose of this study was to evaluate how well the multi-theory model (MTM) can explain both initiation and maintenance of healthy sleep behaviour in medical college students.Methods A convenience sample of medical students from a medical college in the Southeastern USA was recruited for participation in this cross-sectional study. An online survey was used to gather self-reported sociodemographic information as well as variables based on MTM.Results Of the 327 participants, 54.3% were women and 76.7% were White. Over one-third (35.6%) of the medical students reported inadequate sleep. Regression models were created to explain the initiation and sustenance of adequate sleep behaviour among individuals not currently engaging in adequate sleep behaviour. For initiation, participatory dialogue and behavioural confidence were statistically significant and explained 44.4% of the variance in the initiation of adequate sleep behaviour change among medical students. For sustenance, the MTM constructs emotional transformation, practice for change, and changes in the social environment were statistically significant and explained 38.6% of the variance in the continuation of adequate sleep behaviour change.Conclusions The MTM shows promise as a sound theoretical framework to inform the development of intervention programmes focused on behavioural modification to improve sleep quality among medical students.